Parathyroid hormone (PTH)-related protein stimulates Pi secretion across fish proximal tubule cells - Guerreiro, P. M. (2014)
The factors that control Ca2+ and Pi transport in the fish nephron are unclear. In tetrapods these ions are primarily regulated by calcitonin and PTH. Recently several PTH-like proteins were found in fish but their roles are not known. In fish larvae, PTHrP enhanced total Ca2+ uptake, increasing influx and reducing efflux.